2004
DOI: 10.1093/bja/aeh078
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinization of intra-cuff lidocaine and use of gel lubrication protect against tracheal tube-induced emergence phenomena

Abstract: These data show benefits of using an alkalinized lidocaine-filled ETT cuff in combination with water-soluble gel lubrication in preventing post-intubation sore throat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
66
1
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 20 publications
4
66
1
9
Order By: Relevance
“…6 Dehydration and irritation of the mucosa are responsible for mucosal pain following intubation; 19 thus, it is important to monitor pain even after surgery of short duration. In contrast with other studies where 10% lidocaine, sterile water, or water soluble gels were used as lubricants, [7][8][9]18,19 in our study, the outside wall of the cuff membrane was not lubricated prior to its use. The VAS scores monitored in our study were in the low range (B 3/10), similar to those reported by Estebe et al 7,8 or by Navarro et al 19 at one hour and 24 hr.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…6 Dehydration and irritation of the mucosa are responsible for mucosal pain following intubation; 19 thus, it is important to monitor pain even after surgery of short duration. In contrast with other studies where 10% lidocaine, sterile water, or water soluble gels were used as lubricants, [7][8][9]18,19 in our study, the outside wall of the cuff membrane was not lubricated prior to its use. The VAS scores monitored in our study were in the low range (B 3/10), similar to those reported by Estebe et al 7,8 or by Navarro et al 19 at one hour and 24 hr.…”
Section: Discussionmentioning
confidence: 59%
“…The in vitro diffusion rate of alkalinized lidocaine was found to be similar to low-volume/high-pressure cuffs and high-volume/low-pressure cuffs. 8 Other groups have proposed to prefill the ETT cuffs with lidocaine 90 min prior to intubation in order to condition the cuff's semi-permeable membrane. 18,19 This approach could yield interesting results in the case of short duration surgeries, but it remains time-consuming in a day-to-day clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations